1998
DOI: 10.2105/ajph.88.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ectopic pregnancy and previous induced abortion.

Abstract: OBJECTIVES: This study investigated the role of prior history of induced abortion in subsequent ectopic pregnancies. METHODS: Data from two French case-control studies were used to examine the effect of induced abortion on ectopic pregnancy risk. Case patients (n = 570) were women admitted for ectopic pregnancy during the study period; controls (n = 1385) were women who delivered in the same center. RESULTS: The analysis among women with no previous ectopic pregnancy showed that, after control for the main ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
2
21
1
3
Order By: Relevance
“…Multiple induced abortions as risk factor for ectopic pregnancy is well established (11)(12)(13)(14)(15)(16). This finding confirms one of the earlier prospective studies in the department (3) and is consistent with internationally identified risk factor for the overall increase in the incidence of ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple induced abortions as risk factor for ectopic pregnancy is well established (11)(12)(13)(14)(15)(16). This finding confirms one of the earlier prospective studies in the department (3) and is consistent with internationally identified risk factor for the overall increase in the incidence of ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…A large percentage of the patients in the study had one or more induced abortions, which are illegally performed in the community, because of the very restrictive laws on abortion. Multiple induced abortions as risk factor for ectopic pregnancy is well established (11)(12)(13)(14)(15)(16). The study scenario of multiple illegal abortions is coherent as the level of women actively contracepting is low in the society, which also has a restrictive abortion laws in place.…”
Section: Discussionmentioning
confidence: 99%
“…Holt et al (1989) [24] reported that induced abortion does not increase the risk of EP. However, Tharaux-Deneux and her colleagues (1998) [25] wrote that induced abortions did significantly increased the risk of EP in succeeding years. In Saudi Arabia, the practice of induced abortions does not exist.…”
Section: Discussionmentioning
confidence: 99%